10Boron Is Mobile in Cowpea Plants - Silva, Sylvia Leticia Oliveira; Prado, Renato de Mello; Abreu-Junior, Cassio Hamilton; Silva, Gilmara Pereira da; Silva Júnior, Gabriel Barbosa da; Silva, José Lucas Farias da (Frontiers in Plant Science, 2021)
Cowpea [Vigna unguiculata (L.) Walp] is cultivated in tropical and subtropical regions worldwide, but its production is usually limited by boron (B) deficiency, which can be mitigated by applying B via foliar spraying. In plants with nutrient mobility, the residual effect of foliar fertilization increases, which might improve its efficiency. An experiment was carried out to evaluate the concentration and mobility of the B isotopic tracer (10B) in different organs of cowpea plants, after application of this micronutrient in the growing media and also to leaves. Treatments were designed based on B fertilization as follows: without B in the growth media, with 10B applied via foliar spraying (10B-L), with B in the growth media (substrate) and 10B via foliar spraying (10B-L + B-S), and 10B in the growth media (substrate) without foliar spraying (10B-S), in addition to a control without fertilization. A redistribution of 10B was observed in new leaves when the element was supplied via foliar spraying, resulting in greater leaf area, dry mass and dry matter production of aerial parts, and also the whole plant. 10Boron was redistributed when applied via foliar spraying in cowpea plants, regardless of the plant’s nutritional status, which in turn might increase internal B cycling.